Experiences with the management and breeding of Mexican axolotl (Ambystoma mexicanum), for research and biobanking purposes, in a vivarium - Erika Servín; Erika Servín; Alicia Alcantar-Rodriguez; Alfredo Medrano (Frontiers in Amphibian and Reptile Science)
The Mexican axolotl (Ambystoma mexicanum) is widely used in laboratory research around the world, even though it is classified as critically endangered in nature. We review and describe the development of effective management strategies for this species, focusing on cryopreservation and research purposes under laboratory conditions. We share our experiences and challenges in maintaining water quality, feeding, and fostering natural reproduction in captive axolotls. Results indicate that the Mexican axolotl shows promise as a model for biobanking of endangered amphibian species.